WOMEN TRAVELERS PREFERENCES IN HOTEL INDUSTRY AT TIRUNELVELI CITY (International Journal of Food and Nutritional Sciences, 2022)
Hotel industry primarily provide accommodation and secondarily it provides more services to its customers such as lodging, foods and beverages, housekeeping, cab booking etc..In olden days most of the male travelers only preferred hotel stay in their travel time. Women travelers are mostly not interested to stay at hotel alone, In modern world they are ready to staying in hotel alone according to their business, job and education purpose and they prefer some facilities like safety, friendly environment, entertainment etc... In this article the study is made on the Women Travelers Preferences. A sample of 50 women travelers has been selected those who are stayed in hotels at Tirunelveli district. The study focuses which kinds of services were preferred by women travelers from hotels. The collected information suggests the hoteliers should adjust the environment of their hotel according to the women travelers’ preference then they get goodwill and better economic growth in their business sector.